Switching Control Strategy for Greenhouse Temperature-Humidity System Based on Prediction Modeling: A Simulation Study - Xu, Zhenfeng; Chen, Junjie (ITB Journal Publisher, LPPM ITB, 2017)
It is difficult to achieve coordination control of multiple facilities that are driven by on-off actuators in a greenhouse, especially when there is more than one indoor environmental factor to consider at the same time. With the consideration of indoor air temperature and relative humidity, we propose a switching control strategy based on prediction modeling. The operation of the greenhouse system was divided into several modes according to the on-off control characteristics of the available facilities. Then, a switching diagram was designed according to the relationship between the indoor air temperature and humidity and their setting ranges. When the two indoor environmental factors reach their upper or lower limits, IARX models are used to predict them over a specified horizon for each optional mode respectively. Mode switching is carried out based on prediction results. The switching control strategy was simulated based on a mechanistic model of the greenhouse microclimate. The results show that the facilities can be coordinated very well by the proposed control strategy and it is easy to implement. The control strategy is still applicative when more facilities or more indoor environmental factors need to be taken into account.